Room for improvement? : relocating a business school - Angwin, Duncan; Thomas, Matt, 1978- (London : SAGE Publications Ltd, 2016)
The case fbfb the transition of Oxford Brookes' business school to a new building on the university campus outside of the city of Oxford and how management dealt with concerns to do with the new working space and adapted their original design to ensure greater student satisfaction.
Originally published in Angwin, D., & Thomas, M. (2016). Room for improvement? Relocating a business school. In S. Paroutis, L. Heracleous, & D. Angwin (Eds.), Practicing strategy: Texts and cases (2nd ed., pp. 262-278). London, UK: SAGE Publications Ltd. ISBN: 9781473912854.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Oxford Brookes University. -- School of Business -- Buildings